Secondary glaucoma due to the progressive iris atrophy. Century after the first disease dscription. Case report - Jurowski, Piotr; Goś, Roman; Kapica, Andrzej; Zdzieszyńska, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The irydocorneal endothelial syndrome (ICE) consists of some disorders, like: progressive essential iris atrophy, Chandler disease and the iris nevus syndrome that are characterized by corneal endothelium proliferation and migration, iris atrophy, corneal oedema and/or pigmentary iris nevi. Secondary, refractory glaucoma affects about 50% of patients with progressive essential iris atrophy. Medication of glaucoma is only initially effective. Some conventional filtering surgeries, to control glaucoma are often unsuccessful. Presented case of our patient with primary essential iris atrophy, with secondary glaucoma shows surgical problems. Multiple filtration surgery with or without antyproliferative agents turn out not to be sufficient. In conclusion, intraocular pressure was effectively lowered with irydocleisis technique.